Modelling the ejection friction in injection moulding - Correia, Mário Simões (2013)
The quality of parts produced by injection moulding may be affected during the ejection stage of the moulding cycle. At this stage the parts are mechanically forced to separate from the moulding surfaces. The ejection force depends on the shrinkage of the polymer onto the core and on the friction properties of the contacting surfaces at the moment of extraction. As during moulding there is a replication of the part on the mould surface the ejection process is also dependent on the plastic deformation of the moulded material. Ejection takes place in a very short time, hence the static coefficient of friction must be considered for modelling the ejection process. To understand the contribution of the mechanisms involved in friction during the ejection stage, a mixed approach was developed: analytical simulation for the ploughing component, numerical simulation for the deformation mechanism, and an experimental inference for the adhesion. The study was based on the observation of three materials that are commonly used in injection mouldings: polypropylene, polycarbonate and a blend of polycarbonate/acrylonitrile- butadiene. The friction behaviour was studied with two testing methods: a prototype tester that is fitted to a universal testing machine, and an instrumented mould for the characterization of the friction force. The relevance of roughness, temperature and contact pressure on friction was evidenced, on the actual value of the static coefficient of friction that applies in the demoulding of thermoplastic mouldings.